Topology simulation and contact mechanics of bifractal rough surfaces*. (November 2016) - Borri, Claudia; Paggi, Marco
A numerical method to generate bifractal surfaces due to a modification of the slope of the power spectral density function in the low- or high-frequency range is proposed. The method has been applied to simulate real surfaces of Ginkgo Biloba leaf scanned at two different magnifications by matching the corresponding experimental power spectral densities. Slight differences have been found in the statistical distributions of the asperity heights and curvatures for the lowest magnification that had marginal influence on the frictionless normal contact response of the surface. For highest magnification, however, the statistics of the simulated numerical surface were quite different from those of the real one, leading also to a significant difference in the normal contact results.